La construcción y dotación de la iglesia parroquial de Valdealgorfa (Teruel) en la primera mitad del Setecientos: The construction and provision of the parish church of Valdealgorfa (Teruel) in the first half of the Seventeenth century - Martín Marco, Jorge (Artigrama, 2022)
Resumen La iglesia parroquial de la Natividad de Valdealgorfa (Teruel) fue uno de los proyectos arquitectónicos que arrancaron en el Bajo Aragón al filo de 1700. La relectura de la documentación ya publicada y la localización de nuevas referencias procedentes de los archivos locales, permiten completar la historia constructiva del edificio, con la materialización del templo y la torre campanario, esta última, ya en el ecuador del Setecientos. Pero, además, ha sido posible recomponer el proceso de ornamentación de la capilla mayor, un interesante y dilatado proyecto desarrollado en paralelo a la construcción del edificio, en el que se integraron la arquitectura, la escultura y la pintura, y que al final dio lugar al actual retablo mayor, el mejor conservado de una iglesia parroquial del Bajo Aragón. Abstract The parish church of the Nativity of Valdealgorfa (Teruel) was one of the architectural projects that started in Bajo Aragón at the edge of 1700. The re-reading of the documentation already published and the location of new references from the local archives allow the completion of the constructive history of the building, with the materialization of the temple and the bell tower, already in the equator of the 17th century. But, in addition, it has been possible to recompose the process of ornamentation of the main chapel, an interesting and extensive project developed in parallel to the construction of the building, in which architecture, sculpture and painting were integrated, and which in the end gave instead of the current main altarpiece, the best one preserved from a parish church in Bajo Aragón. Keywords Architecture, Sculpture, Baroque, Bajo Aragón, Valdealgorfa.